Developmental and Embryo Axis Regulation of Gibberellin Biosynthesis during Germination and Young Seedling Growth of Pea - Ayele, Belay T. (American Society of Plant Biologists, 2006)
The expression patterns of five genes (PsGA20ox1, PsGA20ox2, PsGA3ox1, PsGA2ox1, and PsGA2ox2) encoding five regulatory gibberellin (GA) biosynthesis enzymes (two GA 20-oxidases, a GA 3β-hydroxylase, and two GA 2β-hydroxylases) were examined to gain insight into how these genes coordinate GA biosynthesis during germination and early postgermination stages of the large-seeded dicotyledonous plant pea (Pisum sativum). At the time the developing embryo fills the seed coat, high mRNA levels of PsGA20ox2 (primarily responsible for conversion of C20-GAs to GA(20)), PsGA2ox1 (primarily responsible for conversion of GA(20) to GA(29)), and PsGA2ox2 (primarily responsible for conversion of GA(1) to GA(8)) were detected in the seeds, along with high GA(20) and GA(29) levels, the enzymatic products of these genes. Embryo maturation was accompanied by a large reduction in PsGA20ox2 and PsGA2ox1 mRNA and lower GA(20) and GA(29) levels. However, PsGA2ox2 transcripts remained high. Following seed imbibition, GA(20) levels in the cotyledons decreased, while PsGA3ox1 mRNA and GA(1) levels increased, implying that GA(20) was being used for de novo synthesis of GA(1). The presence of the embryo axis was required for stimulation of cotyledonary GA(1) synthesis at the mRNA and enzyme activity levels. As the embryo axis doubled in size, PsGA20ox1 and PsGA3ox1 transcripts increased, both GA(1) and GA(8) were detectable, PsGA2ox2 transcripts decreased, and PsGA2ox1 transcripts remained low. Cotyledonary-, root-, and shoot-specific expression of these GA biosynthesis genes and the resultant endogenous GA profiles support a key role for de novo GA biosynthesis in each organ during germination and early seedling growth of pea.